Analisis Sebaran Emisi SO₂ dan NO₂ dari Cerobong Boiler Industri Pengolahan Kelapa Sawit dengan Model AERMOD di PT Perkebunan Nusantara VI Unit Usaha Pinang Tinggi, Kabupaten Muaro Jambi - Aprilia, Arifa; Anggraini, Febri Juita; Yasdi, Yasdi (Teknik Lingkungan Universitas Islam Indonesia, 2025)
PT Perkebunan Nusantara VI Unit Usaha Pinang Tinggi uses biomass fuel that can produce the main pollutants, SO2 and NO2, dispersed around industry and have the potential to cause air pollution. The study using the AERMOD model aims to determine dispersion of SO2 and NO2 concentrations at receptors, validation of the AERMOD model with RMSPE, contribution of boiler chimney emission to the receptors, and dispersion of actual unmeasured receptor concentration compared to air quality standards. The results showed that the highest and lowest dispersion of SO2 at 1-hour in Kantin Karyawan PKS was 35,85 μg/m3 and Kantor & Gudang was 26,85 μg/m3, while at 24-hours in Halaman Kantor PKS was 25,72 μg/m3 and Perumahan Karyawan PKS (Pondok 5) was 23,99 μg/m3. The highest and lowest dispersion of NO2 at 1-hour in Kantin Karyawan PKS was 115,64 μg/m3 and Kantor & Gudang was 38,77 μg/m3, while at 24-hours in Kantin Karyawan PKS was 36,36 μg/m3 and Perumahan Karyawan PKS (Pondok 5) was 24,36 μg/m3. AERMOD model validation for SO2 19,94%<25% (valid) and NO2>25% (invalid). The highest and lowest chimney emission contribution of SO2 at 1-hour in Halaman Kantor PKS was 10,35% and Halaman Toko Bu Sakti was 0%, while at 24-hours in Halaman Kantor PKS was 6,77% and Perumahan Karyawan PKS (Pondok 5) was 0,62%. The highest and lowest contribution of NO2 at 1-hour in Halaman Kantor PKS was 18,46% and Halaman Toko Bu Sakti was 0%, while at 24-hours in Halaman Kantor PKS was 30,12% and Perumahan Karyawan PKS was 0,92%. The actual unmeasured receptors are smaller than the ambient air quality standards.